Putin's Oil : The Yukos Affair and the Struggle for Russia - Sixsmith, Martin (New York Continuum, 2010)
The story of Russia's energy wars and their consequences, focusing on Mikhail Khodorkovsky, owner of Yukos, which was once the country's biggest oil firm and key to the Russian economy
Keywords: Petroleum industry and trade -- Russia (Federation) -- Energy policy -- Russia (Federation) -- Businesspeople -- Russia (Federation) -- Malicious prosecution